Chick chorioallantoic membrane as an in vivo model for the study of angiogenesis and lymphangiogenesis - Wan, Zhenzhen; Hirche, Christoph; Fricke, Fabia; Dragu, Adrian; Will-Marks, Patrick (Journal of vascular research, 2024)
Background: The high incidence of vascular and lymphatic metastasis is closely associated with poor prognosis and mortality in cancer. Finding effective inhibitors to prevent pathological angiogenesis and lymphangiogenesis relies on appropriate in vivo models. The chick embryo chorioallantoic membrane (CAM) is formed by the fusion of the chorion and allantois during embryonic development. Summary: In this context, we primarily summarize the changes in vascular and lymphatic vessel formation in tumors under the action of drugs using this model, providing a preclinical model basis for effective tumor inhibitors. Key Messages: Due to natural immunological defects, chick embryos accept various tissue and species transplants without immune response. The CAM model has been widely used in studying angiogenesis, antiangiogenesis, tumor growth, tumor metastasis, and drug efficacy. This review describes the use of CAM assays as a valuable method for testing the in vivo effects of drugs on vascular and lymphatic vessel formation before further investigating the effects of drugs on tumor vessels and lymphatic vessels in animal models.
Gesehen am 25.09.2025